Impact of the Expression System on Recombinant Protein Production in Escherichia coli BL21 - Lozano Terol, Gema; Gallego-Jara, Julia; Sola Martínez, Rosa Alba; Martínez Vivancos, Adrián; Cánovas Díaz, Manuel; de Diego Puente, Teresa (Frontiers in Microbiology, 2021)
Recombinant protein production for medical, academic, or industrial applications is essential for our current life. Recombinant proteins are obtained mainly through microbial fermentation, being Escherichia coli the host most used. In spite of that, some problems are associated with the production of recombinant proteins in E. coli, as the formation of inclusion bodies, the metabolic burden, or the inefficient translocation/transport system of expressed proteins. Optimizing transcription of heterologous genes is essential to avoid these drawbacks and develop competitive biotechnological processes. Here, expression of YFP reporter protein is evaluated under the control of four promoters of different strength (PT7lac, Ptrc, Ptac and PBAD) and two different replication origins (high copy number pMB1’ and low copy number p15A). In addition, the study has been carried out with E. coli BL21 wt, and the ackA mutant strain growing in a rich medium with glucose or glycerol as carbon sources. Results showed that metabolic burden associated to transcription and translation of foreign genes involves a decrease of recombinant protein expression. It is necessary to find a balance between plasmid copy number and promoter strength to maximize soluble recombinant protein expression. The results obtained represent an important advance on the most suitable expression system to improve both the quantity and quality of recombinant proteins in bioproduction engineering.